RESILIENSI SPIRITUAL PASANGAN MUSLIM YANG TIDAK DIKARUNIAI ANAK: REKONSTRUKSI MAKNA SAKINAH, MAWADDAH, WA RAHMAH DI TENGAH STIGMA SOSIAL - NAQIYYAH SALSABILA; Sakha Fadhila Qurrotul Aini; Heni Ani Nuraeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research analyzes the phenomenon of spiritual resilience among Muslim couples who are not blessed with children in Indonesia. Amidst social constructions that position offspring as the primary validation of marital happiness, these couples face significant challenges in the form of stigma and social pressure. Through an observational study, this research explores how the values of Sakinah, Mawaddah, and wa Rahmah are reconstructed as instruments of mental and spiritual strength. The results indicate that marital happiness in Islam is comprehensive and does not solely rely on the aspect of procreation, but rather on tranquility of the soul (sakinah), true love (mawaddah), and social devotion (rahmah).